APPLICATION OF THE DECOMPOSITION METHOD FOR SOLVING THE FIVE-INDEX TRANSPORTATION PROBLEM IN LOGISTIC SYSTEMS - Акімов, Дмитро (Modern engineering and innovative technologies, 2025)
This article examines the application of the decomposition method for solving the five-index distribution problem of the transportation type in information logistics systems. This problem models the process of optimal allocation of goods flows in complex